Adoption of Islamic banking in a non-Islamic country: evidence from Uganda. Issue 5 (20th January 2020) - Bananuka, Juma; Katamba, David; Nalukenge, Irene; Kabuye, Frank; Sendawula, Kasimu
Abstract : Purpose: This paper aims to examine the concept and practice of Islamic banking in the context of a non-Islamic country such as Uganda. Design/methodology/approach: Semi-structured interviews were used to elicit the strategies banks may use to ensure that the Islamic banking system is successful and to ascertain those factors that may hinder its success. Chief executive officers of business associations, heads of committees on Islamic banking and religious leaders were interviewed. Findings: The strategies used by financial institutions in ensuring the adoption of Islamic banking are now known such as "creating awareness of Islamic banking's mode of operation among existing and potential clients." The findings also show that factors such as "lack of trust among clients" may hinder the success of Islamic banking. Research limitations/implications: The research findings are useful for informing the deliberations of regulators, the business community and financial institutions. The results are applicable only to those countries in the preparation stages of adopting Islamic banking services for the first time, but they could be generalized to any new product launch in any country. Originality/value: This paper may help Ugandan financial institutions to design strategies that will accelerate the adoption and, ultimately, the diffusion of Islamic banking in Uganda.